Canal de crédito: um estudo sobre a influência das questões regulatórias no mercado de crédito brasileiro - Anker, Tomás (2005)
The literature has been discussing for a long time the influence of monetary policy in the achievement of certain employment and GDP levels. At the same time, throughout the last decades, it appeared in this same literature a discussion concerning the monetary policy transmission channels for the long-term. Among the set of channels pointed out by this literature, the credit channel is one which has been receiving a lot of attention from scholars willing to deepen the knowledge of its process and its relationships with the monetary and real economy. Due to these facts, this work intends to find evidences of the presence of a credit channel in Brazil which works through endogenous changes of the credit market, more specifically the ones occurring into the agents’ balancesheets and on their agency costs, what contribute to the decrease of the credit balance supplied to these borrowers. More than that, through the empirical tests here conducted, this work intends to find evidences that the credit channel in Brazil is stronger due to the existence of banking regulatory rules which turn them more conservator in the supply of marginal credits to the set of new borrowers and to the ones which have credits already taken. This test assumes as the variable the series of credit balances supplied throughout the years, constructed according to the Central Bank rules that establish loss provision criteria and which is supposedly capable of being changed after a monetary push which worsen the balancesheet quality of borrowers forcing the financial institutions to reclassify borrowers to lower risk classes. This reclassification may increase the credits which are most penalized with the highest loss provision rates, what turns the bankers into more conservator agents and less willing to supply credit to the set of higher-risk borrowers and to the borrowers as a whole.